New treatments for hepatitis C virus (HCV): scope for preventing liver disease and HCV transmission in England. Issue 8 (29th March 2016) - Harris, R. J.; Martin, N. K.; Rand, E.; Mandal, S.; Mutimer, D.; Vickerman, P.; Ramsay, M. E.; De Angelis, D.; Hickman, M.; Harris, H.E.
Summary: New direct‐acting antivirals have the potential to transform the hepatitis C (HCV) treatment landscape, with rates of sustained viral response in excess of 90%. As these new agents are expensive, an important question is whether to focus on minimizing the consequences of severe liver disease, or reducing transmission via 'treatment as prevention'. A back‐calculation model was used to estimate the impact of treatment of mild, moderate and compensated cirrhosis on incident cases of HCV‐related end‐stage liver disease/hepatocellular carcinoma (ESLD/HCC). In addition, a dynamic model was used to determine the impact on incidence and prevalence of chronic infection in people who inject drugs (PWID), the main risk group in England. Treating 3500 cirrhotics per year was predicted to reduce ESLD/HCC incidence from 1100 (95% CrI 970–1240) cases per year in 2015 to 630 (95% CrI 530–770) in 2020, around half that currently expected, although treating moderate‐stage disease will also be needed to sustain this reduction. Treating mild‐stage PWID was required to make a substantial impact on transmission: with 2500 treated per year, chronic prevalence/annual incidence in PWID was reduced from 34%/4.8% in 2015 to 11%/1.4% in 2030. There was little overlap between the two goals: treating mild stage had virtually no impact on ESLD/HCC within 15 years, but the long timescale of liver disease means relatively few PWID reach cirrhosis before cessation of injecting. Strategies focussing on treating advanced disease have the potential for dramatic reductions in severe morbidity, but virtually no preventative impact.